The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/0001-3765201520140518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cigarette smoke condensate on the production and characterization of exopolysaccharides by Bifidobacterium

Abstract: The aim of the study was to investigate the effect of cigarette smoke on the production and characterization of exopolysaccharides (EPSs) produced by Bifidobacterium. Cigarettes of Shanhua brand (nicotine: 1.1 mg, tar: 11 mg) were utilized to prepare a cigarette smoke condensate (CSC). The standard strain of Bifidobacterium animalis was cultured in MRS media under anaerobic addition of CSC. The results showed that CSC significantly decreased the growth of B. animalis as well as EPSs and acetic acid production.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
2
8
1
1
Order By: Relevance
“…Although a causal relationship between SCFAs and protection in this study was not confirmed, both cigarette smoke 95 and environmental particulate matter 96 reduced SCFA concentrations in rodents, and cigarette smoke condensate reduced their production in vitro 90 .…”
Section: [H3] Microbiota and Copdcontrasting
confidence: 74%
See 1 more Smart Citation
“…Although a causal relationship between SCFAs and protection in this study was not confirmed, both cigarette smoke 95 and environmental particulate matter 96 reduced SCFA concentrations in rodents, and cigarette smoke condensate reduced their production in vitro 90 .…”
Section: [H3] Microbiota and Copdcontrasting
confidence: 74%
“…The causes of smoking-associated changes in microbiome composition are likely a combination of environmental, host and microbial changes such as intestinal and immune disruption, impaired clearance of pathogens 84,85 , acidification of gastric contents 86 and ingestion of bacteria that occur in cigarettes 87 . Furthermore, cigarette smoke can directly affect the virulence of both bacteria 88 and fungi 89 , as well as altering the growth and exopolysaccharide structure of known gut bacteria such as Bifidobacterium animalis 90 , which may contribute to dysbiosis. Even following smoking cessation, many of these changes that cause dysbiosis persist for prolonged periods, and thus any therapeutic intervention to restore the microbiota may potentially require repeated administration to avoid relapse.…”
Section: [H3] Microbiota and Copdmentioning
confidence: 99%
“…The fact as mentioned above that cigarette smoke or side-stream smoking decreases the amount of Bifidobacterium [124], mainly butyrate-producing bacteria with anti-inflammatory and anti-tumor molecule role [172] was highly consistent with the results that butyrate-producing bacteria are depleted in cancer patients [170]. In addition, in vitro and in vivo studies found that cigarette smoke not only decrease the fecal abundance of Bifidobacterium but also reduce its production of short chain fatty acids (SCFAs) [124, 173], immune-regulatory molecules modulating immune and inflammatory response within many diseases, and reductions in the concentration of SCFAs especially butyrate in colorectal tissues were demonstrated to be associated with the possibility of early stage CRC development [174]. Moreover, the smoking-related microbial changes may lead to altered epithelial mucin composition of the mucus layer and increased inflammatory response [175], which play pivotal role in the onset of CRC.…”
Section: Introductionsupporting
confidence: 54%
“…132 In addition, some in vitro and animal studies found that cigarette smoke might decrease the fecal abundance of Bifidobacterium and reduce its production of SCFAs. 133, 134 …”
Section: Smokingmentioning
confidence: 99%